PUBLIC AWARENESS ABOUT HIV PREVENTION MEASURES - Sargsjane, Jeļena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Human immunodeficiency virus (HIV), which, when progressing, develops as acquired immunodeficiency syndrome (AIDS), has been known worldwide for over 30 years. It is one of the greatest epidemics that mankind has ever encountered. The number of HIV infections also increases in Latvia each year, as evidenced by official data from the Center for Disease Prevention and Control. In turn, information on infection with AIDS mechanisms, prevention measures is readily available in the mass media, medical institutions, etc. It also determined the purpose of the study - is the public well informed about HIV infection and its preventive measures?